Informal caregiving patterns and trajectories of psychological distress in the UK Household Longitudinal Study. Issue 10 (12th September 2018) - Lacey, Rebecca E.; McMunn, Anne; Webb, Elizabeth
Abstract: Background: Approximately seven million people in the UK are engaged in informal caregiving. Informal caregivers are at risk of poorer mental and physical health. However, less is known about how the relationship between the informal caregiving and psychological distress changes over time. The aim of this study was to investigate longitudinal associations between the informal caregiving and psychological distress amongst UK men and women aged 16+. Methods: Data were analysed from the UK Household Longitudinal Study (UKHLS, n = 9368), a nationally representative study of UK households. Longitudinal linear mixed modelling was used to estimate associations between the longitudinal patterns of informal caregiving (non-caregiver/one episode of 1–2 years/intermittent caregiving/3+ years caregiving) and trajectories of psychological distress across seven waves of UKHLS data. Results: Informal caregiving was not associated with psychological distress for men. Women engaged in long-term (⩾3 years) or intermittent caregiving had higher levels of psychological distress at the point of initiation, compared with women who were not caregivers throughout the study period (3+ years caregiver: regression coefficient 0.48, 95% confidence interval (CI) 0.07–0.89; intermittent caregiver: regression coefficient 0.47, 95% CI 0.02–0.92). Trajectories of psychological distress changed little over time, suggesting a plateau effect for these caregiving women. Conclusions: Women engaged in long-term or repeated shorter episodes of informal caregiving reported more symptoms of psychological distress than non-caregiving women. Given the increased risk of reporting psychological distress and the increasing importance of the informal care sector, the risk of poorer mental health of informal caregivers should be a priority for public health.